(untitled) (Papeles, 2024)
Based on two ethnographic investigations carried out in different parts of the Cordoba prison universe, we will focus on the state management of the deaths that occur in the prisons of Cordoba and the know-how that is articulated in their claim and processing. In addition, we will observe how these learnings and the consequences of imprisonment are modulated by other agencies that promote other languages and ways of talking to the State. This research focused on analyzing the tutelary actions of the Patronato del Liberado de Córdoba, where training was provided to obtain microcredits. The other research focused on deaths in prisons in Cordoba, paying attention to the institutional networks used by different agents to deal with them and the strategies developed. From the dialogue between these investigations, in this article we will focus on how the language of the claim and the plea was modulated by the people who passed through the prisons in the different stages of their prison experiences, by their relatives and by the lawyers who accompanied their cases. We will also consider how this language was modulated, or pretended to be modulated, by the administrators of the Patronato and other agents of the state of Córdoba in training sessions for released prisoners.